Glue of PMMA with viscosity controlled by glacial acetic acid and preparation method thereof
Patent Information
- Application Number
- CN202610247380.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-02
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-03-02
AI Technical Summary
如公开号为CN119775930A的中国专利公开了一种PMMA基丙烯酸酯胶粘剂,但存在着通过增加PMMA固含量提高固化后强度时黏度急剧上升导致施工困难的问题
1.实现低黏度施工与高强度固化的协同优化:通过游离冰醋酸与PMMA分子链的氢键作用降低体系初始黏度,结合PMMA包覆冰醋酸微胶囊在干燥过程中的缓释调控,使胶水在施工阶段保持500至50000mPa·s的可调黏度范围,确保良好的流动性、润湿性和渗透性,同时在冰醋酸最终挥发后形成高固含PMMA胶膜,表现出优异的内聚强度和抗蠕变性能,解决了传统PMMA胶水施工性能与固化性能难以兼得的问题。
Smart Images

Figure CN121950212B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesives, and more specifically to a PMMA adhesive with viscosity controlled by glacial acetic acid and its preparation method. Background Technology
[0002] Polymethyl methacrylate (PMMA) adhesives, due to their excellent transparency, weather resistance, bonding strength, and good adhesion to various substrates, have irreplaceable application value in fields such as optical device assembly, acrylic bonding, electronic component encapsulation, and precision instrument repair. In practical applications, PMMA adhesives need to meet several performance requirements: First, in terms of application performance, the adhesive must have an appropriate viscosity to facilitate coating, penetration, and wetting of the substrate surface. Excessive viscosity can lead to difficulties in coating, air bubbles, and insufficient filling of joints, while excessively low viscosity, although beneficial for application, may result in insufficient cohesive strength after curing. Second, in terms of post-curing performance, the adhesive film formed must possess high cohesive strength, good creep resistance, and long-term stable mechanical properties to ensure reliable long-term use under high-stress environments. Third, in terms of storage stability, the adhesive must maintain stable viscosity during storage, without significant thickening or stratification. Meeting and developing these performance requirements is of great significance for broadening the application range of PMMA adhesives, improving the reliability of bonded structures, and promoting technological progress in related industries.
[0003] However, current PMMA adhesives suffer from the following shortcomings. For example, Chinese patent CN119775930A discloses a PMMA-based acrylate adhesive, but it suffers from a problem where increasing the PMMA solid content to improve post-curing strength leads to a sharp increase in viscosity, causing difficulties in application. Similarly, Chinese patent CN112266748A discloses an acrylic adhesive and its preparation method, but it suffers from a problem where reducing the viscosity of PMMA results in a decrease in the creep resistance of the cured adhesive film. The root cause of these shortcomings lies in the fact that traditional PMMA adhesives rely on a single mechanism of solvent-based viscosity adjustment. This mechanism cannot effectively balance low-viscosity application with high-strength curing, rapid drying with low-defect appearance, and stable storage with adjustable viscosity during use. It lacks an intelligent control mechanism that can maintain low viscosity during application, dynamically compensate for viscosity changes during drying, and achieve high strength after curing. Summary of the Invention
[0004] The purpose of this invention is to provide a PMMA adhesive with viscosity controlled by glacial acetic acid and its preparation method, thereby solving the technical problems of current PMMA adhesives that are difficult to achieve simultaneously between low viscosity and easy application and high cohesive strength / creep resistance after drying, high solids content and high strength adhesive film and defoaming / low defect appearance during rapid evaporation and drying, and the inherent mechanistic conflict between the system's storage viscosity stability and the time-varying rheological control requirements based on free glacial acetic acid and microcapsule sustained release.
[0005] This invention employs a dual mechanism: synergistic viscosity reduction by free glacial acetic acid and PMMA matrix combined with sustained-release regulation by PMMA-encapsulated glacial acetic acid microcapsules. Free glacial acetic acid reduces the initial viscosity of the system through solvation of the PMMA molecular chains, achieving ease of application. The gradual release of glacial acetic acid from the microcapsules during drying compensates for the viscosity increase caused by solvent evaporation, extending degassing time and reducing defects. Finally, the formation of a high-solids-content PMMA film after the final evaporation of glacial acetic acid achieves high cohesive strength and creep resistance. This demonstrates a synergistic effect between application and curing performance, rather than a single optimization, achieving a unified approach of low-viscosity application, controllable rheological processes, and high-strength curing.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A PMMA adhesive with viscosity controlled by glacial acetic acid, the adhesive comprising, by weight: PMMA 10–25 parts by weight; 2–15 parts by weight of glacial acetic acid; Solvent system 50–100 parts by mass; and 0.5–10 parts by weight of PMMA-coated glacial acetic acid microcapsule component after drying; The solvent system is selected from one or both of ethyl acetate and acetone; the 10–25 parts by weight of PMMA do not include PMMA in the microcapsule component, the 2–15 parts by weight of glacial acetic acid do not include glacial acetic acid in the microcapsule component, and the 50–100 parts by weight of the solvent system do not include residual solvent in the microcapsule component; furthermore, the adhesive is applied at a temperature of 25°C and a shear rate of [missing information]. The viscosity measured by a rotational viscometer under the specified conditions is 500–50000 mPa·s, and the viscosity is adjusted by changing the specific amount of glacial acetic acid in the range of 2–15 parts by mass.
[0007] Furthermore, the PMMA-coated glacial acetic acid microcapsule component is prepared through the following steps: A1. Preparation of the oil phase: Add 5–20 parts by weight of PMMA to 80–200 parts by weight of ethyl acetate and stir to dissolve, thus obtaining the PMMA oil phase; A2, preparation and emulsification of the core phase: 5-40 parts by weight of glacial acetic acid are added to the PMMA oil phase, and sheared for 2-10 minutes at a shearing speed of 3000-10000 r / min to obtain a pre-emulsion with a core material dispersion. A3, Preparation of aqueous phase: Add 2-20 parts by weight of polyvinyl alcohol to 200-1000 parts by weight of deionized water and stir to dissolve to obtain the polyvinyl alcohol aqueous phase; A4, Encapsulation and Desolventizing: The pre-emulsion is added to the polyvinyl alcohol aqueous phase and stirred for 10–60 min at a stirring speed of 300–1500 r / min to form an emulsion. Then, ethyl acetate is removed at a temperature of 20–45℃ and an absolute pressure of 0.01–0.08 MPa until the cumulative recovered ethyl acetate reaches 90–99% of the mass of the ethyl acetate fed into the feed. A5, Post-processing: After solid-liquid separation, the obtained system is washed with deionized water 1–5 times and dried at a temperature of 35–55℃ and an absolute pressure of 0.005–0.03MPa for 4–24h to obtain the PMMA-coated glacial acetic acid microcapsule component. Furthermore, the quality control parameters for the PMMA-coated glacial acetic acid microcapsule component are as follows: particle size of 1–80 µm, encapsulation rate of glacial acetic acid of 10–60%, wherein the encapsulation rate is the ratio of the mass of glacial acetic acid in the microcapsule component to the mass of glacial acetic acid fed into the feed, and the residual ethyl acetate is not higher than 0.5 wt%, wherein the wt% is based on the total mass of the dried microcapsule component.
[0008] Furthermore, in the PMMA-coated glacial acetic acid microcapsule component, the mass ratio of glacial acetic acid to PMMA is 0.5:1–3:1, where the mass of glacial acetic acid is the mass of glacial acetic acid in the microcapsule component, and the mass of PMMA is the mass of PMMA, the shell material of the microcapsule; in step A3, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous phase is 0.2–9.1 wt%, and the mass fraction is calculated as: (mass of polyvinyl alcohol / (mass of polyvinyl alcohol + mass of deionized water)) × 100%; in step A4, the time for removing ethyl acetate is 0.5–6 h.
[0009] Furthermore, the solvent system consists of one or both of ethyl acetate and acetone, and the sum of the mass parts of ethyl acetate and acetone is 50–100 parts by mass, wherein ethyl acetate is 50–100 parts by mass and acetone is 0–50 parts by mass.
[0010] Furthermore, the mass ratio of 2–15 parts by mass of glacial acetic acid to 10–25 parts by mass of PMMA is 0.08:1–0.8:1.
[0011] As a concept of this invention, the design employing the synergistic effect of free glacial acetic acid and PMMA molecular chains to reduce system viscosity primarily aims to enhance the balance between application and curing performance. Glacial acetic acid, as a polar small-molecule solvent, can form hydrogen bonds with PMMA side-chain ester groups through its carboxyl groups, effectively weakening the entanglement between PMMA molecular chains and reducing the apparent viscosity of the system. This allows the adhesive to maintain good flowability and wettability even at low temperatures or under conditions of high PMMA solid content. Simultaneously, the evaporation rate of glacial acetic acid is significantly slower than that of ethyl acetate and acetone, maintaining a low viscosity state in the early stages of drying after coating, extending the degassing time window, and reducing the formation of air bubbles within the adhesive film. More importantly, the introduction of PMMA-coated glacial acetic acid microcapsules enables the slow-release regulation of glacial acetic acid. During adhesive drying, the microcapsules gradually release the encapsulated glacial acetic acid driven by the solvent concentration gradient and osmotic pressure, compensating for the viscosity increase caused by the evaporation of the main solvent. This allows the system to maintain a suitable rheological state for a longer period, ensuring sufficient degassing and substrate wetting. After the solvent and glacial acetic acid have completely evaporated, the high-solids PMMA film forms a dense polymer phase, exhibiting excellent cohesive strength and creep resistance. This achieves synergistic optimization of low-viscosity application and high-strength curing, and has significant performance advantages over traditional solutions that use high solvent content for viscosity reduction or low molecular weight PMMA alone.
[0012] This invention also discloses a method for preparing PMMA adhesive with viscosity controlled by glacial acetic acid, characterized by comprising the following steps: S1 provides PMMA-coated glacial acetic acid microcapsule components; S2, Preparation of adhesive masterbatch: Add 10–25 parts by weight of PMMA to 50–100 parts by weight of solvent system and stir to dissolve, to obtain adhesive masterbatch without glacial acetic acid and without microcapsule components, wherein the solvent system is selected from one or both of ethyl acetate and acetone; S3, Add glacial acetic acid: Add 2-15 parts by weight of glacial acetic acid to the glue stock solution and mix; S4, Add microcapsule component: Add 0.5–10 parts by weight of the PMMA-coated glacial acetic acid microcapsule component to the system obtained in step S3 and mix evenly to obtain the adhesive; In step S3, the amount of glacial acetic acid is controlled to ensure that the resulting adhesive is maintained at 25°C and a shear rate of... The viscosity was adjusted to 500–50000 mPa·s under the specified conditions.
[0013] Furthermore, the dissolution temperature in step S2 is 20–50°C and the dissolution time is 0.5–8 h; the temperature at which the microcapsule component is added in step S4 is 15–35°C; and the solvent system in step S2 is composed of one or both of ethyl acetate and acetone, and the sum of the mass parts of ethyl acetate and acetone is 50–100 parts by mass, wherein ethyl acetate is 50–100 parts by mass and acetone is 0–50 parts by mass.
[0014] Furthermore, the addition time of glacial acetic acid in step S3 is 1–20 min, and the mixing time in step S4 is 5–60 min.
[0015] Furthermore, in step S4, after the mixture is homogeneous, it is degassed for 10–30 minutes under vacuum conditions with an absolute pressure of 0.01–0.08 MPa.
[0016] Furthermore, in step A1, the stirring and dissolution are carried out at a temperature of 20–50°C and a stirring speed of 200–800 r / min for 0.5–8 h until PMMA is completely dissolved to form a transparent, homogeneous oil phase without visible solid particles.
[0017] Furthermore, in step A2, shear emulsification is performed at a temperature of 15–30°C.
[0018] Furthermore, in step A3, after adding polyvinyl alcohol to deionized water, it is heated and stirred for 0.5–3 hours at a temperature of 60–90°C and a stirring speed of 200–600 r / min until the polyvinyl alcohol is completely dissolved to form a homogeneous aqueous phase without visible undissolved particles.
[0019] Furthermore, in step A4, ethyl acetate is removed by vacuum distillation and recovered by a condenser.
[0020] Furthermore, when the solid-liquid separation in step A5 is carried out by centrifugation, the centrifugation speed is 3000–8000 r / min and the centrifugation time is 5–20 min; when the solid-liquid separation is carried out by filtration, the solid-liquid separation is carried out by vacuum filtration through a filter membrane with a pore size of 0.45 µm.
[0021] Furthermore, in step A5, the amount of deionized water used for each wash is 2–10 times the total mass of the dried microcapsule components.
[0022] Furthermore, the adhesive is applied at a temperature of 25°C and a shear rate of [missing information]. Under these conditions, the viscosity measured by a rotational viscometer is 500–50000 mPa·s.
[0023] Furthermore, by changing the specific amount of glacial acetic acid within the range of 2–15 parts by mass, the adhesive is prepared at a temperature of 25°C and a shear rate of [missing information]. Under these conditions, the viscosity measured by a rotational viscometer falls within the range of 500–50000 mPa·s.
[0024] Furthermore, in step S2, the dissolution is carried out under the condition of stirring speed of 200–800 r / min.
[0025] Furthermore, both steps S3 and S4 are performed at a stirring speed of 100–500 r / min.
[0026] Furthermore, after the microcapsule component is added to the glue mother liquor, and stirred for 30 minutes at a temperature of 25°C and a stirring speed of 100–500 r / min, microcapsule particles with a particle size of 1–80 µm can still be observed through an optical microscope.
[0027] Furthermore, the mass of glacial acetic acid in the microcapsules is determined by titration after the dried microcapsule components are completely dissolved in acetone.
[0028] Furthermore, after adding glacial acetic acid in step S3, the mixture is stirred at a temperature of 15–35°C to obtain an adhesive system without visible layering.
[0029] Furthermore, during the viscosity test, the sample is degassed under vacuum before testing and measured using a rotational viscometer.
[0030] As another aspect of this invention, a stepwise preparation method is employed, which involves first preparing a glue stock solution free of glacial acetic acid and then gradually adding free glacial acetic acid and microcapsule components. This method primarily enhances the precision of viscosity control and the system's storage stability. First, a stock solution of PMMA in a solvent system is prepared to establish a stable polymer solution base system, avoiding interference from glacial acetic acid on the dissolution behavior of PMMA during the initial dissolution stage. Subsequently, the viscosity is quantitatively controlled by precisely controlling the amount of glacial acetic acid added. Utilizing the linear relationship between the strength of the hydrogen bonding interaction between glacial acetic acid and PMMA and its concentration, the viscosity can be precisely adjusted within a wide range of 500 to 50000 mPa·s, meeting the differentiated viscosity requirements of various construction processes. Finally, the microcapsule components are added and mixed under mild conditions to ensure that the microcapsules are uniformly dispersed in the glue and do not prematurely break down and release due to excessive shear or temperature fluctuations, ensuring that the slow-release control function of the microcapsules is effectively utilized in practical applications. This step-by-step feeding sequence also avoids the problems of osmotic pressure imbalance and decreased encapsulation rate that may be caused by the simultaneous addition of glacial acetic acid and microcapsules, and eliminates air bubbles introduced during the preparation process through the vacuum degassing step, thereby improving the uniformity and reliability of the finished adhesive.
[0031] In this invention, free glacial acetic acid and PMMA-coated glacial acetic acid microcapsules have distinct functional focuses and synergistic effects in the adhesive system. Free glacial acetic acid focuses on providing immediate viscosity reduction and initial application flowability, rapidly lowering system viscosity through hydrogen bonding with PMMA molecular chains, ensuring wettability and penetration of the adhesive during coating. The PMMA-coated glacial acetic acid microcapsules focus on providing dynamic viscosity compensation and long-term regulation during the drying process, gradually releasing glacial acetic acid during solvent evaporation through a slow-release mechanism, extending the low-viscosity defoaming time window. Regarding improved application performance, free glacial acetic acid reduces the degree of entanglement between PMMA chains through solvation, while the slow-released glacial acetic acid from the microcapsules further compensates for viscosity increases; their synergistic effect allows the system to maintain a suitable application viscosity for a longer period. Regarding improved curing performance, free glacial acetic acid completely evaporates without residue in the later stages of drying, and the glacial acetic acid released from the microcapsules also evaporates, ultimately forming a high-solids-content PMMA film. Their synergistic effect ensures high cohesive strength and creep resistance after curing. The synergistic effect of the two is reflected in the fact that free glacial acetic acid provides a rapid response to the initial viscosity control, while microcapsules provide stable viscosity maintenance during the drying process. Together, they construct a three-stage synergistic control mechanism of low viscosity during the construction stage, controllable rheology during the drying process, and high strength after curing. This has a better balance between construction performance and curing performance than the solution that uses free glacial acetic acid alone or microcapsules alone.
[0032] Beneficial technical effects 1. Achieving synergistic optimization of low-viscosity application and high-strength curing: The initial viscosity of the system is reduced through hydrogen bonding between free glacial acetic acid and PMMA molecular chains. Combined with the slow-release regulation of PMMA-coated glacial acetic acid microcapsules during the drying process, the adhesive maintains an adjustable viscosity range of 500 to 50,000 mPa·s during the application stage, ensuring good flowability, wettability, and permeability. At the same time, after the glacial acetic acid finally evaporates, a high-solids-content PMMA film is formed, exhibiting excellent cohesive strength and creep resistance. This solves the problem of traditional PMMA adhesives being unable to simultaneously achieve both application and curing performance.
[0033] 2. Extending the degassing time window and reducing film defects: During solvent evaporation, the microcapsules gradually release the encapsulated glacial acetic acid driven by the concentration gradient and osmotic pressure, effectively compensating for the sharp increase in viscosity caused by the rapid evaporation of the main solvent. This allows the system to maintain a suitable rheological state for a longer period of time, providing sufficient time for bubble removal, significantly reducing the formation of internal bubble defects and surface pinhole defects in the film, and improving the appearance quality and mechanical reliability of the adhesive structure.
[0034] 3. Achieving precise viscosity adjustment and storage stability: By controlling the specific amount of glacial acetic acid within the range of 2 to 15 parts by mass, and utilizing the linear relationship between the strength and concentration of hydrogen bonding between glacial acetic acid and PMMA, precise quantitative control of viscosity can be achieved over a wide range to meet the differentiated viscosity requirements of different substrates and construction processes. At the same time, a stepwise preparation method is adopted, in which the adhesive masterbatch is prepared first and then glacial acetic acid and microcapsules are added gradually, to avoid the problem of osmotic pressure imbalance between glacial acetic acid and microcapsules, ensuring that the viscosity of the adhesive remains stable and the integrity of the microcapsules is well maintained during storage.
[0035] 4. Improved process operability and cost-effectiveness: The conventional emulsification-solvent evaporation method is used to prepare microcapsules, which is simple and cost-controllable. The microcapsule particle size can be controlled within the range of 1 to 80 µm, the encapsulation rate can reach 10 to 60%, and the residual ethyl acetate is no more than 0.5 wt%, which meets the requirements of industrial production. The glue preparation process does not require special equipment, the feeding sequence is clear, and the viscosity control has good reproducibility, making it suitable for large-scale applications.
[0036] 5. Expanding application scope and improving bonding reliability: The adhesive of this invention has the combined advantages of low viscosity application, controllable rheological process and high strength curing. It is particularly suitable for application scenarios with strict requirements for construction performance and curing quality, such as optical device assembly, precision electronic packaging and transparent material bonding. It significantly improves the long-term reliability and service life of the bonded structure and promotes the technological progress of PMMA adhesive in the field of high-end manufacturing. Attached Figure Description
[0037] Figure 1 The particle size difference distribution q(d) diagrams for Example 1 and Comparative Example 7 are shown.
[0038] Figure 2 The cumulative particle size distribution Q(d) diagrams for Example 1 and Comparative Example 7 are shown.
[0039] Figure 3 The images show the superimposed FTIR spectra of Example 1 and Comparative Example 6.
[0040] Figure 4 The DSC diagrams are for Example 1 and Comparative Example 3.
[0041] Figure 5 This is a physical image of the PMMA adhesive with viscosity controlled by glacial acetic acid in Example 1.
[0042] Figure 6 This is a scanning electron microscope image of the PMMA-coated glacial acetic acid microcapsule component from Example 1.
[0043] Figure 7 This is a transmission electron microscope image of the PMMA-coated glacial acetic acid microcapsule component from Example 1. Detailed Implementation
[0044] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0045] Example 1 This embodiment provides a PMMA adhesive with viscosity controlled by glacial acetic acid. The adhesive, by weight, comprises: 17 parts PMMA, 8 parts glacial acetic acid, 75 parts solvent system, and 5 parts dried PMMA-coated glacial acetic acid microcapsule component. The solvent system consists of 60 parts ethyl acetate and 15 parts acetone, with a total weight of 75 parts ethyl acetate and acetone. The 17 parts PMMA do not include the PMMA in the microcapsule component, the 8 parts glacial acetic acid do not include the glacial acetic acid in the microcapsule component, and the 75 parts solvent system do not include residual solvent in the microcapsule component. The adhesive of this embodiment is suitable for use at a temperature of 25°C and a shear rate of [missing information]. Under the specified conditions, the viscosity measured by a rotational viscometer was 15000 mPa·s. In this embodiment, the viscosity was controlled by changing the specific amount of glacial acetic acid within the range of 2-15 parts by mass. In this embodiment, the mass ratio of 8 parts by mass of glacial acetic acid to 17 parts by mass of PMMA was 0.47:1, which meets the requirement of a range of 0.08:1 to 0.8:1.
[0046] The PMMA-coated glacial acetic acid microcapsule component of this embodiment was prepared through the following steps: Step A1, preparing the oil phase: 12 parts by mass of PMMA were added to 140 parts by mass of ethyl acetate, and stirred at 35°C and a stirring speed of 500 r / min for 4 hours until the PMMA was completely dissolved to form a transparent, homogeneous oil phase without visible solid particles, thus obtaining the PMMA oil phase; Step A2, preparing and emulsifying the core phase: 22 parts by mass of glacial acetic acid were added to the PMMA oil phase of this embodiment, and sheared and emulsified at 22°C and a shearing speed of 6500 r / min for 6 minutes to obtain a pre-emulsion with a dispersed core material; Step A3, preparing the aqueous phase: 10 parts by mass of polyvinyl alcohol were added to 600 parts by mass of deionized water, and heated and stirred at 75°C and a stirring speed of 400 r / min for 1.5 hours until the polyvinyl alcohol was completely dissolved to form a homogeneous aqueous phase without visible undissolved particles, thus obtaining the polyvinyl alcohol aqueous phase. In this embodiment, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous phase was 1.64%. The mass fraction (wt%) is calculated by dividing the mass of polyvinyl alcohol by the sum of the mass of polyvinyl alcohol and the mass of deionized water, and then multiplying by 100%, meeting the range requirement of 0.2-9.1 wt%. Step A4, encapsulation and desolvation: The pre-emulsion of this embodiment is added to the aqueous phase of polyvinyl alcohol in this embodiment, and stirred for 35 minutes at a stirring speed of 850 r / min to form an emulsion. Then, ethyl acetate is removed by vacuum distillation at a temperature of 32℃ and an absolute pressure of 0.045 MPa, and the ethyl acetate is recovered through a condenser for 3 hours until the cumulative recovered ethyl acetate mass reaches 95% of the ethyl acetate mass added. Step A5, post-treatment: The obtained system is subjected to solid-liquid separation by centrifugation at a speed of 5500 r / min for 12 minutes. Then, it is washed three times with deionized water, with the amount of deionized water used each time being 6 times the total mass of the dried microcapsule components. The system is then dried for 14 hours at a temperature of 45℃ and an absolute pressure of 0.018 MPa to obtain the PMMA-coated glacial acetic acid microcapsule components of this embodiment.
[0047] The quality control parameters for the PMMA-coated glacial acetic acid microcapsule component in this embodiment are as follows: particle size of 40 µm, encapsulation efficiency of glacial acetic acid of 35%, wherein the encapsulation efficiency is the ratio of the mass of glacial acetic acid in the microcapsule component to the mass of glacial acetic acid in the feed, and residual ethyl acetate of 0.25 wt%. In this embodiment, wt% is based on the total mass of the dried microcapsule component. The mass ratio of glacial acetic acid to PMMA in the PMMA-coated glacial acetic acid microcapsule component in this embodiment is 0.64:1. This ratio is calculated by dividing 7.7 parts by mass of glacial acetic acid in the microcapsule component by 12 parts by mass of PMMA, which meets the requirement of a range of 0.5:1 to 3:1.
[0048] The PMMA adhesive with viscosity controlled by glacial acetic acid in this embodiment is prepared by the following method: Step S1, providing PMMA-coated glacial acetic acid microcapsule component; Step S2, preparing adhesive stock solution, adding 17 parts by mass of PMMA to 75 parts by mass of solvent system, stirring and dissolving for 4 hours at 35°C and 500 r / min to obtain adhesive stock solution without glacial acetic acid and without microcapsule component, wherein the solvent system in this embodiment consists of 60 parts by mass of ethyl acetate and 15 parts by mass of acetone; Step S3, adding glacial acetic acid, adding 8 parts by mass of glacial acetic acid to the adhesive stock solution in this embodiment at 25°C over a 10-minute addition time, and mixing at 300 r / min to obtain an adhesive system without visible layering; Step S4, adding microcapsule component, adding 5 parts by mass of the PMMA-coated glacial acetic acid microcapsule component of this embodiment to the system obtained in step S3 at 25°C, and mixing at 300 r / min to obtain an adhesive system without visible layering; Mix for 30 minutes at a shear rate of 0.045 MPa. After thorough mixing, degas for 20 minutes under vacuum conditions to obtain the adhesive of this embodiment. In this embodiment, the amount of glacial acetic acid is controlled to ensure that the resulting adhesive is suitable for use at 25°C and a shear rate of 0.045 MPa. The viscosity was adjusted to 15000 mPa·s under the specified conditions. In this embodiment, after the microcapsule component was added to the glue mother liquor, it was stirred for 30 minutes at 25°C and 300 r / min. Microcapsule particles with a diameter of 40 µm could still be observed under an optical microscope. The mass of glacial acetic acid in the microcapsules of this embodiment was determined by titration after the dried microcapsule component was completely dissolved in acetone. For the viscosity test in this embodiment, the sample underwent vacuum degassing before testing, and the viscosity was measured using a rotational viscometer.
[0049] Technical features of Example 1: This example uses moderate parameter configurations: 17 parts by mass of PMMA, 8 parts by mass of glacial acetic acid, 75 parts by mass of solvent system (ethyl acetate to acetone ratio of 4:1), and 5 parts by mass of microcapsule component. All parameters are selected within the 40-60% range to achieve a moderate viscosity of 15000 mPa·s. The microcapsule preparation process uses appropriate process conditions, achieving an encapsulation efficiency of 35% and a particle size of 40 µm, ensuring the stability and sustained-release effect of the microcapsules. The mass ratio of glacial acetic acid to PMMA is 0.47:1, which is within a reasonable control range, ensuring both suitable initial viscosity and providing potential for viscosity increase after microcapsule rupture. The parameter combination in this example exhibits good stability and repeatability, and the mild process conditions are suitable for large-scale production.
[0050] Application Scenarios: This embodiment is suitable for bonding applications requiring moderate initial viscosity and controllable viscosity improvement, such as the assembly and bonding of electronic components, the positioning and fixing of optical lenses, and the structural bonding of precision instruments. During application, it exhibits moderate fluidity and wettability, facilitating coating and positioning. The microcapsules gradually rupture under mechanical stress or solvent action, releasing glacial acetic acid, achieving a gradual increase in viscosity and extending the working time window. It is particularly suitable for medium-precision assembly processes that require both high initial viscosity and high final strength.
[0051] Example 2 This embodiment provides a PMMA adhesive with viscosity controlled by glacial acetic acid. The adhesive, by weight, comprises: 22 parts PMMA, 12 parts glacial acetic acid, 60 parts solvent system, and 7 parts dried PMMA-coated glacial acetic acid microcapsule component. The solvent system consists of 50 parts ethyl acetate and 10 parts acetone, with a total weight of 60 parts ethyl acetate and acetone. The 22 parts PMMA do not include the PMMA in the microcapsule component, the 12 parts glacial acetic acid do not include the glacial acetic acid in the microcapsule component, and the 60 parts solvent system do not include residual solvent in the microcapsule component. The adhesive of this embodiment is suitable for use at a temperature of 25°C and a shear rate of [missing information]. Under the specified conditions, the viscosity measured by a rotational viscometer was 35000 mPa·s. In this embodiment, the viscosity was controlled by changing the specific amount of glacial acetic acid within the range of 2-15 parts by mass. In this embodiment, the mass ratio of 12 parts by mass of glacial acetic acid to 22 parts by mass of PMMA was 0.545:1, which meets the requirement of a range of 0.08:1 to 0.8:1.
[0052] The PMMA-coated glacial acetic acid microcapsule component of this embodiment was prepared through the following steps: Step A1, preparing the oil phase: 16 parts by mass of PMMA were added to 110 parts by mass of ethyl acetate, and stirred at 42°C and 650 r / min for 6 hours until the PMMA was completely dissolved to form a transparent, homogeneous oil phase without visible solid particles, thus obtaining the PMMA oil phase; Step A2, preparing and emulsifying the core phase: 32 parts by mass of glacial acetic acid were added to the PMMA oil phase of this embodiment, and sheared and emulsified at 26°C and 8000 r / min for 8 minutes to obtain a pre-emulsion with a dispersed core material; Step A3, preparing the aqueous phase: 15 parts by mass of polyvinyl alcohol were added to 380 parts by mass of deionized water, and heated and stirred at 82°C and 500 r / min for 2.2 hours until the polyvinyl alcohol was completely dissolved to form a homogeneous aqueous phase without visible undissolved particles, thus obtaining the polyvinyl alcohol aqueous phase. In this embodiment, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous phase was 3.80%. The mass fraction (wt%) is calculated by dividing the mass of polyvinyl alcohol (PVA) by the sum of the mass of PVA and the mass of deionized water, and then multiplying by 100%, meeting the range requirement of 0.2-9.1 wt%. Step A4, encapsulation and desolvation, involves adding the pre-emulsion of this embodiment to the aqueous phase of PVA and stirring for 45 minutes at 1100 r / min to form an emulsion. Then, ethyl acetate is removed by vacuum distillation at 38°C and 0.025 MPa, and recovered via a condenser for 4.5 hours until the cumulative recovered ethyl acetate reaches 97% of the initial ethyl acetate mass. Step A5, post-treatment, involves centrifugation to separate the solid and liquid components at 6500 r / min for 16 minutes. The system is then washed four times with deionized water, each wash using eight times the total mass of the dried microcapsule components, at 50°C and 0.012 MPa. The PMMA-coated glacial acetic acid microcapsule component of this embodiment was obtained by drying at MPa for 18 hours.
[0053] The quality control parameters for the PMMA-coated glacial acetic acid microcapsule component in this embodiment are as follows: particle size of 55 µm, encapsulation efficiency of glacial acetic acid of 45%, wherein the encapsulation efficiency is the ratio of the mass of glacial acetic acid in the microcapsule component to the mass of glacial acetic acid in the feed, and residual ethyl acetate of 0.15 wt%. In this embodiment, wt% is based on the total mass of the dried microcapsule component. The mass ratio of glacial acetic acid to PMMA in the PMMA-coated glacial acetic acid microcapsule component in this embodiment is 0.9:1. This ratio is calculated by dividing 14.4 parts by mass of glacial acetic acid in the microcapsule component by 16 parts by mass of PMMA, which meets the requirement of a range of 0.5:1 to 3:1.
[0054] The PMMA adhesive with viscosity controlled by glacial acetic acid in this embodiment is prepared by the following method: Step S1, providing PMMA-coated glacial acetic acid microcapsule component; Step S2, preparing adhesive stock solution, adding 22 parts by mass of PMMA to 60 parts by mass of solvent system, stirring and dissolving for 6 hours at 42°C and 650 r / min to obtain adhesive stock solution without glacial acetic acid and without microcapsule component, wherein the solvent system in this embodiment consists of 50 parts by mass of ethyl acetate and 10 parts by mass of acetone; Step S3, adding glacial acetic acid, adding 12 parts by mass of glacial acetic acid to the adhesive stock solution in this embodiment at 30°C over a 15-minute addition time, and mixing at 400 r / min to obtain an adhesive system without visible layering; Step S4, adding microcapsule component, adding 7 parts by mass of the PMMA-coated glacial acetic acid microcapsule component of this embodiment to the system obtained in step S3 at 28°C, and mixing at 350 r / min. Mix for 45 minutes at a shear rate of 0.025 MPa. After thorough mixing, degas for 25 minutes under vacuum conditions to obtain the adhesive of this embodiment. In this embodiment, the amount of glacial acetic acid is controlled to ensure that the resulting adhesive is suitable for use at 25°C and a shear rate of 0.025 MPa. The viscosity was adjusted to 35000 mPa·s under the specified conditions. In this embodiment, after the microcapsule component was added to the glue stock solution, it was stirred for 30 minutes at 25°C and 350 r / min. Microcapsule particles with a diameter of 55 µm could still be observed under an optical microscope. The mass of glacial acetic acid in the microcapsules of this embodiment was determined by titration after the dried microcapsule component was completely dissolved in acetone. For the viscosity test in this embodiment, the sample underwent vacuum degassing before testing, and the viscosity was measured using a rotational viscometer.
[0055] Technical Features of Example 2: This example employs a formulation design with high PMMA and high glacial acetic acid content. The PMMA content is 22 parts by mass, the glacial acetic acid content is 12 parts by mass, the solvent system is 60 parts by mass, and the microcapsule component is 7 parts by mass. The main parameters are selected within the range of 55-80%, achieving a high viscosity of 35000 mPa·s. A relatively low solvent system is used, with an ethyl acetate to acetone ratio of 5:1, resulting in a relatively high solid content, which is beneficial for improving the initial strength and adhesion of the adhesive. Microcapsule preparation utilizes a high shear speed of 8000 r / min and a long emulsification time of 8 minutes, achieving an encapsulation efficiency of 45% and a particle size of 55µm, storing a significant amount of sustained-release glacial acetic acid. The mass ratio of glacial acetic acid to PMMA is 0.545:1, which is moderately high. The ratio of glacial acetic acid to PMMA in the microcapsules is 0.9:1, indicating a large sustained-release capacity. This embodiment, through a higher solid content and a higher amount of glacial acetic acid, provides stronger ability to control viscosity in the later stages while ensuring the initial viscosity.
[0056] Application Scenarios: This embodiment is suitable for applications requiring high initial viscosity and strong bond strength, such as structural bonding, fixation of load-bearing components, and assembly under high stress environments. The high PMMA and solids content give the adhesive excellent initial bond strength and mechanical properties, while the high glacial acetic acid content and microcapsule content provide long-lasting viscosity control. Under complex stress conditions, the microcapsules gradually rupture to release glacial acetic acid, achieving dynamic optimization of viscosity and strength. It is particularly suitable for industrial applications requiring high-strength bonding and long-term performance, such as bonding automotive parts, bonding metals and plastics, and permanent fixation of high-precision optical components.
[0057] Example 3 This embodiment provides a PMMA adhesive with viscosity controlled by glacial acetic acid. The adhesive, by weight, comprises: 13 parts PMMA, 4 parts glacial acetic acid, 88 parts solvent system, and 2 parts dried PMMA-coated glacial acetic acid microcapsule component. The solvent system consists of 70 parts ethyl acetate and 18 parts acetone, with the sum of the weights of ethyl acetate and acetone being 88 parts. The 13 parts PMMA do not include the PMMA in the microcapsule component, the 4 parts glacial acetic acid do not include the glacial acetic acid in the microcapsule component, and the 88 parts solvent system do not include residual solvent in the microcapsule component. The adhesive of this embodiment is suitable for use at a temperature of 25°C and a shear rate of [missing information]. Under the specified conditions, the viscosity measured by a rotational viscometer was 3000 mPa·s. In this embodiment, the viscosity was adjusted by changing the specific amount of glacial acetic acid within the range of 2-15 parts by mass. In this embodiment, the mass ratio of 4 parts by mass of glacial acetic acid to 13 parts by mass of PMMA was 0.308:1, which meets the requirement of a range of 0.08:1 to 0.8:1.
[0058] The PMMA-coated glacial acetic acid microcapsule component of this embodiment was prepared through the following steps: Step A1, preparing the oil phase: 8 parts by mass of PMMA were added to 170 parts by mass of ethyl acetate, and stirred at 28°C and 350 r / min for 2 hours until the PMMA was completely dissolved to form a transparent, homogeneous oil phase without visible solid particles, thus obtaining the PMMA oil phase; Step A2, preparing and emulsifying the core phase: 21 parts by mass of glacial acetic acid were added to the PMMA oil phase of this embodiment, and sheared and emulsified at 20°C and 4500 r / min for 4 minutes to obtain a pre-emulsion with a dispersed core material; Step A3, preparing the aqueous phase: 6 parts by mass of polyvinyl alcohol were added to 800 parts by mass of deionized water, and heated and stirred at 68°C and 300 r / min for 1 hour until the polyvinyl alcohol was completely dissolved to form a homogeneous aqueous phase without visible undissolved particles, thus obtaining the polyvinyl alcohol aqueous phase. In this embodiment, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous phase was 0.74%. The mass fraction (wt%) is calculated by dividing the mass of polyvinyl alcohol by the sum of the mass of polyvinyl alcohol and the mass of deionized water, and then multiplying by 100%, meeting the range requirement of 0.2-9.1 wt%. Step A4, encapsulation and desolvation: The pre-emulsion of this embodiment is added to the aqueous phase of polyvinyl alcohol in this embodiment, and stirred for 22 minutes at a stirring speed of 600 r / min to form an emulsion. Then, ethyl acetate is removed by vacuum distillation at a temperature of 26℃ and an absolute pressure of 0.06 MPa, and the ethyl acetate is recovered through a condenser for 1.5 hours until the cumulative recovered ethyl acetate mass reaches 92% of the ethyl acetate mass added. Step A5, post-treatment: The obtained system is subjected to solid-liquid separation by centrifugation at a speed of 4000 r / min for 8 minutes. It is then washed twice with deionized water, with the amount of deionized water used each time being 4 times the total mass of the dried microcapsule components. The system is then dried for 8 hours at a temperature of 40℃ and an absolute pressure of 0.022 MPa to obtain the PMMA-coated glacial acetic acid microcapsule components of this embodiment.
[0059] The quality control parameters for the PMMA-coated glacial acetic acid microcapsule component in this embodiment are as follows: particle size of 20 µm, encapsulation rate of glacial acetic acid of 20%, wherein the encapsulation rate is the ratio of the mass of glacial acetic acid in the microcapsule component to the mass of glacial acetic acid in the feed, and residual ethyl acetate of 0.35 wt%. In this embodiment, the wt% is based on the total mass of the dried microcapsule component. The mass ratio of glacial acetic acid to PMMA in the PMMA-coated glacial acetic acid microcapsule component in this embodiment is 0.525:1. This ratio is calculated by dividing 4.2 parts by mass of glacial acetic acid in the microcapsule component by 8 parts by mass of PMMA, which meets the requirement of a range of 0.5:1 to 3:1.
[0060] The PMMA adhesive with viscosity controlled by glacial acetic acid in this embodiment is prepared by the following method: Step S1, providing PMMA-coated glacial acetic acid microcapsule component; Step S2, preparing adhesive stock solution, adding 13 parts by mass of PMMA to 88 parts by mass of solvent system, stirring and dissolving for 2 hours at 28°C and 350 r / min to obtain adhesive stock solution without glacial acetic acid and without microcapsule component, wherein the solvent system in this embodiment consists of 70 parts by mass of ethyl acetate and 18 parts by mass of acetone; Step S3, adding glacial acetic acid, adding 4 parts by mass of glacial acetic acid to the adhesive stock solution in this embodiment at 20°C over a 5-minute addition time, and mixing at 200 r / min to obtain an adhesive system without visible layering; Step S4, adding microcapsule component, adding 2 parts by mass of PMMA-coated glacial acetic acid microcapsule component of this embodiment to the system obtained in step S3 at 20°C, and mixing at 200 r / min. Mix for 15 minutes at a shear rate of 0.06 MPa. After thorough mixing, degas for 12 minutes under a vacuum of 0.06 MPa to obtain the adhesive of this embodiment. In this embodiment, the amount of glacial acetic acid is controlled to ensure that the resulting adhesive is suitable for use at 25°C and a shear rate of 0.06 MPa. The viscosity was adjusted to 3000 mPa·s under the specified conditions. In this embodiment, after the microcapsule component was added to the glue stock solution, it was stirred for 30 minutes at 25°C and 200 r / min. Microcapsule particles with a diameter of 20 µm could still be observed under an optical microscope. The mass of glacial acetic acid in the microcapsules of this embodiment was determined by titration after the dried microcapsule component was completely dissolved in acetone. For the viscosity test in this embodiment, the sample underwent vacuum degassing before testing, and the viscosity was measured using a rotational viscometer.
[0061] Technical Features of Example 3: This example employs a low-solids, high-flowability formulation design. The composition includes 13 parts by mass of PMMA, 4 parts by mass of glacial acetic acid, 88 parts by mass of solvent, and 2 parts by mass of microcapsule components. The amounts of PMMA and glacial acetic acid are within the 15-20% range, and the solvent content is within the 76% range, achieving a low viscosity of 3000 mPa·s. The relatively high solvent content, with an ethyl acetate to acetone ratio of approximately 4:1, contributes to the adhesive's excellent flowability and wetting properties. Microcapsule preparation utilizes a low shear speed of 4500 r / min and a short emulsification time of 4 minutes, achieving an encapsulation rate of 20% and a particle size of 20 µm. The microcapsules are small and uniformly dispersed. The mass ratio of glacial acetic acid to PMMA is 0.308:1, which is moderately low, resulting in low initial viscosity and facilitating penetration and spreading. This example, through its high solvent content and low solids content design, provides excellent application convenience and penetration ability while ensuring basic adhesive performance.
[0062] Application Scenarios: This embodiment is suitable for bonding applications requiring low initial viscosity and high flowability, such as penetration bonding of porous materials, capillary filling of micro-gaps, thin-layer coating, and spray application. Low viscosity allows the adhesive to quickly wet the substrate surface, penetrating into tiny pores and gaps to form a uniform adhesive layer. The lower acetic acid and microcapsule content reduces initial viscosity, facilitating precise control of coating thickness and application location. The microcapsules gradually release acetic acid through solvent evaporation or mechanical action, achieving a gradual increase in viscosity and ensuring the final strength of the adhesive layer. It is particularly suitable for applications requiring deep penetration and uniform coating, such as conformal coating of electronic circuit boards, bonding and finishing of textiles, surface treatment of paper, and penetration reinforcement of wood.
[0063] Example 4 This embodiment provides a PMMA adhesive with viscosity controlled by glacial acetic acid. The adhesive, by weight, comprises: 24 parts PMMA, 3 parts glacial acetic acid, 53 parts solvent system, and 9 parts dried PMMA-coated glacial acetic acid microcapsule component. The solvent system consists of 53 parts ethyl acetate, with 0 parts acetone. The 24 parts PMMA do not include the PMMA in the microcapsule component, the 3 parts glacial acetic acid do not include the glacial acetic acid in the microcapsule component, and the 53 parts solvent system do not include residual solvent from the microcapsule component. The adhesive of this embodiment is suitable for use at a temperature of 25°C and a shear rate of... Under the specified conditions, the viscosity measured by a rotational viscometer was 45000 mPa·s. In this embodiment, the viscosity was controlled by changing the specific amount of glacial acetic acid within the range of 2-15 parts by mass. In this embodiment, the mass ratio of 3 parts by mass of glacial acetic acid to 24 parts by mass of PMMA was 0.125:1, which meets the requirement of a range of 0.08:1 to 0.8:1.
[0064] The PMMA-coated glacial acetic acid microcapsule component of this embodiment was prepared through the following steps: Step A1, preparing the oil phase: 18 parts by mass of PMMA were added to 88 parts by mass of ethyl acetate, and stirred at 47°C and a stirring speed of 700 r / min for 7 hours until the PMMA was completely dissolved to form a transparent, homogeneous oil phase without visible solid particles, thus obtaining the PMMA oil phase; Step A2, preparing and emulsifying the core phase: 36 parts by mass of glacial acetic acid were added to the PMMA oil phase of this embodiment, and sheared and emulsified at 18°C and a shearing speed of 9000 r / min for 9 minutes to obtain a pre-emulsion with a dispersed core material; Step A3, preparing the aqueous phase: 18 parts by mass of polyvinyl alcohol were added to 220 parts by mass of deionized water, and heated and stirred at 85°C and a stirring speed of 550 r / min for 2.7 hours until the polyvinyl alcohol was completely dissolved to form a homogeneous aqueous phase without visible undissolved particles, thus obtaining the polyvinyl alcohol aqueous phase. In this embodiment, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous phase was 7.56%. The mass fraction (wt%) is calculated by dividing the mass of polyvinyl alcohol by the sum of the mass of polyvinyl alcohol and the mass of deionized water, and then multiplying by 100%, meeting the range requirement of 0.2-9.1 wt%. Step A4, encapsulation and desolvation: The pre-emulsion of this embodiment is added to the aqueous phase of polyvinyl alcohol in this embodiment, and stirred for 55 minutes at a stirring speed of 400 r / min to form an emulsion. Then, ethyl acetate is removed by vacuum distillation at a temperature of 42℃ and an absolute pressure of 0.015 MPa, and the ethyl acetate is recovered through a condenser. The removal time is 5.5 hours until the cumulative recovered ethyl acetate mass reaches 98% of the ethyl acetate mass added. Step A5, post-treatment: The obtained system is subjected to solid-liquid separation by centrifugation at a speed of 7500 r / min for 18 minutes. Then, it is washed 5 times with deionized water, with the amount of deionized water used each time being 9 times the total mass of the dried microcapsule components, at a temperature of 52℃ and an absolute pressure of 0.008 MPa. The PMMA-coated glacial acetic acid microcapsule component of this embodiment was obtained by drying at MPa for 22 hours.
[0065] The quality control parameters for the PMMA-coated glacial acetic acid microcapsule component in this embodiment are as follows: particle size of 70 µm, encapsulation efficiency of glacial acetic acid of 55%, wherein the encapsulation efficiency is the ratio of the mass of glacial acetic acid in the microcapsule component to the mass of glacial acetic acid in the feed, and residual ethyl acetate of 0.08 wt%. In this embodiment, wt% is based on the total mass of the dried microcapsule component. The mass ratio of glacial acetic acid to PMMA in the PMMA-coated glacial acetic acid microcapsule component in this embodiment is 1.1:1. This ratio is calculated by dividing 19.8 parts by mass of glacial acetic acid in the microcapsule component by 18 parts by mass of PMMA, which meets the requirement of a range of 0.5:1 to 3:1.
[0066] The PMMA adhesive with viscosity controlled by glacial acetic acid in this embodiment is prepared by the following method: Step S1, providing PMMA-coated glacial acetic acid microcapsule component; Step S2, preparing adhesive stock solution, adding 24 parts by mass of PMMA to 53 parts by mass of solvent system, stirring and dissolving for 7 hours at 47°C and 700 r / min to obtain adhesive stock solution without glacial acetic acid and without microcapsule component, wherein the solvent system in this embodiment consists of 53 parts by mass of ethyl acetate; Step S3, adding glacial acetic acid, adding 3 parts by mass of glacial acetic acid to the adhesive stock solution in this embodiment at 32°C over an 18-minute addition time, and mixing at 450 r / min to obtain an adhesive system without visible layering; Step S4, adding microcapsule component, adding 9 parts by mass of the PMMA-coated glacial acetic acid microcapsule component of this embodiment to the system obtained in step S3 at 32°C, and mixing at 450 r / min. Mix for 55 minutes at a shear rate of 0.015 MPa. After thorough mixing, degas under vacuum for 28 minutes to obtain the adhesive of this embodiment. In this embodiment, the amount of glacial acetic acid is controlled to ensure that the resulting adhesive is suitable for use at 25°C and a shear rate of 0.015 MPa. The viscosity was adjusted to 45000 mPa·s under the specified conditions. In this embodiment, after the microcapsule component was added to the glue stock solution, it was stirred for 30 minutes at 25°C and 450 r / min. Microcapsule particles with a diameter of 70 µm could still be observed under an optical microscope. The mass of glacial acetic acid in the microcapsules of this embodiment was determined by titration after the dried microcapsule component was completely dissolved in acetone. For the viscosity test in this embodiment, the sample underwent vacuum degassing before testing, and the viscosity was measured using a rotational viscometer.
[0067] Technical Features of Example 4: This example employs a formulation design with multiple parameters close to the technical solution range. The amount of PMMA is 24 parts by mass, close to the upper end of the 25 parts by mass range; the amount of glacial acetic acid is 3 parts by mass, close to the lower end of the 2 parts by mass range; the solvent system is 53 parts by mass, close to the lower end of the 50 parts by mass range; and the microcapsule component is 9 parts by mass, close to the upper end of the 10 parts by mass range, achieving a high viscosity of 45000 mPa·s. The solvent system uses a single ethyl acetate without acetone, achieving the highest solid content and imparting extremely high initial viscosity and adhesive strength to the adhesive. The microcapsule preparation uses a combination of process parameters including a high shear speed of 9000 r / min, a long emulsification time of 9 minutes, a high encapsulation rate of 55%, and a large particle size of 70 µm. The microcapsules store a large amount of sustained-release glacial acetic acid. The mass ratio of glacial acetic acid to PMMA is 0.125:1, which is relatively low, but the ratio of glacial acetic acid to PMMA in the microcapsules reaches 1.1:1, demonstrating the highly efficient microcapsule sustained-release design. This embodiment, through the combination of high PMMA content, low solvent content, and high microcapsule content, provides a powerful long-term viscosity control capability on the basis of extremely high initial viscosity.
[0068] Application Scenarios: This embodiment is suitable for high-end applications requiring extremely high initial viscosity and ultra-strong bond strength, such as permanent bonding of load-bearing structural components, structural reinforcement under high stress environments, heavy-duty bonding of metal substrates, and lamination bonding of composite materials. The extremely high PMMA and solids content gives the adhesive excellent initial bond strength, creep resistance, and mechanical properties, enabling it to withstand large static and dynamic loads. The high microcapsule content and high encapsulation rate provide a long-lasting and powerful viscosity regulation reserve. During long-term service, the microcapsules gradually rupture to release glacial acetic acid, compensating for performance degradation caused by stress relaxation or microcracks, achieving self-healing and long-term stability of the bond performance. It is particularly suitable for critical applications with stringent long-term reliability requirements, such as bonding aerospace components, bonding rail transit vehicle structures, bonding wind turbine blade composite materials, and sealing building curtain wall structures.
[0069] Comparative Example 1: It is basically the same as Example 1, except that the amount of PMMA used is 8 parts by mass, while the amounts of other components and preparation conditions remain unchanged.
[0070] Comparative Example 2: It is basically the same as Example 1, except that the amount of PMMA used is 28 parts by mass, while the amounts of other components and preparation conditions remain unchanged.
[0071] Comparative Example 3: It is basically the same as Example 1, except that the amount of glacial acetic acid used is 1 part by mass, while the amounts of other components and preparation conditions remain unchanged.
[0072] Comparative Example 4: It is basically the same as Example 1, except that the amount of glacial acetic acid used is 17 parts by mass, while the amounts of other components and preparation conditions remain unchanged.
[0073] Comparative Example 5: It is basically the same as Example 1, except that the amount of microcapsule component is 0.2 parts by mass, while the amount of other components and preparation conditions remain unchanged.
[0074] Comparative Example 6: Basically the same as Example 1, except that no microcapsule component was added, while the amounts of other components and preparation conditions remained unchanged.
[0075] Comparative Example 7: Basically the same as Example 1, except that the shearing speed in microcapsule preparation step A2 is 1500 r / min, resulting in a microcapsule particle size of 150 µm and an encapsulation rate of 8%. The amounts of other components and preparation conditions remain unchanged.
[0076] Comparative Example 8: It is basically the same as Example 1, except that the solvent system uses 75 parts by mass of acetone and does not contain ethyl acetate, while the amounts of other components and preparation conditions remain unchanged.
[0077] Performance testing: Experiment 1: Initial Viscosity Test Test subject: PMMA adhesive sample of the present invention. Test purpose: To evaluate the adhesive at 25°C and shear rate. The initial viscosity under certain conditions was determined to verify the viscosity-regulating effect of glacial acetic acid. Test principle: Apparent viscosity was calculated based on the relationship between shear stress and shear rate determined using a rotational viscometer. Experimental method: The adhesive sample was degassed under vacuum before testing. An appropriate amount of sample was placed in the sample cell of the rotational viscometer. The temperature was set to 25±0.5℃. A rotor matching the viscosity range of the sample was selected, and the shear rate was set to... After the readings stabilize, record the viscosity values. Each sample is tested in triplicate. Key parameters: test temperature 25℃, shear rate... Sample pretreatment involved vacuum degassing. Data processing: The results were expressed as the arithmetic mean ± standard deviation of three tests, with viscosity measured in mPa·s.
[0078] Experiment 2: Storage Viscosity Stability Test Test Subject: PMMA adhesive sample of this invention. Test Objective: To evaluate the viscosity stability of the adhesive under sealed storage conditions and verify the inhibitory effect of microcapsules on viscosity fluctuations during storage. Test Principle: The rheological stability of the system is evaluated by comparing the difference between the initial viscosity and the viscosity after storage. Experimental Method: The adhesive sample was placed in a sealed glass bottle and stored for 7 days at a temperature of 25±2℃ in the dark. During storage, the sample bottle was gently shaken every 24 hours to simulate transportation vibration. After storage, the viscosity was measured according to the method in Experiment 1, and the viscosity change rate was calculated by comparing it with the initial viscosity. Key Parameters: Storage temperature 25℃, storage time 7 days, test conditions the same as in Experiment 1. Data Processing: Viscosity change rate = (viscosity after storage - initial viscosity) / initial viscosity × 100%, taking the average of 3 samples ± standard deviation.
[0079] Experiment 3: Shear Strength Test Test Object: The bonded joint formed after the PMMA adhesive of this invention has cured. Test Objective: To evaluate the bond strength after adhesive curing and verify the balance between low-viscosity application and high-strength bonding. Test Principle: A tensile load is applied to a single lap bonded joint using a tensile testing machine, and the maximum stress at bond failure is measured. Experimental Method: An aluminum alloy substrate with dimensions of 25 mm × 100 mm × 2 mm is prepared. After sanding and cleaning with acetone, the adhesive is applied to the lap surface after drying. The lap area is 25 mm × 12.5 mm. After clamping, it is cured for 72 hours at 25°C and 50% relative humidity. After curing, a shear strength test is performed at a tensile rate of 5 mm / min, and the maximum load is recorded. Key Parameters: Lap area 312.5 mm², curing time 72 hours, tensile rate 5 mm / min. Data Processing: Shear strength = maximum load / lap area, unit: MPa, average value ± standard deviation of 5 joints.
[0080] Experiment 4: Creep Resistance Test Test Object: The bonded joint formed after the PMMA adhesive of this invention has cured. Test Objective: To evaluate the creep resistance of the cured adhesive under continuous load and verify the effectiveness of the high cohesive strength design. Test Principle: The strain of the bonded joint over time is measured under constant stress to assess the long-term stability of the material. Experimental Method: The bonded joint was prepared according to the method in Experiment 3. After curing for 72 hours, a constant load equivalent to 30% of the shear strength was applied on a creep testing machine. The load was continuously applied for 24 hours at 25°C and 50% relative humidity. Displacement was recorded every hour, and creep strain was calculated. Key Parameters: Load was 30% of the shear strength; test temperature was 25°C; test time was 24 hours. Data Processing: Creep strain = 24-hour displacement / initial overlap length × 100%, taken as the average value ± standard deviation of three joints.
[0081] Experiment 5: Microcapsule rupture and release kinetics test Test Subject: Samples of PMMA-coated glacial acetic acid microcapsules dispersed in an adhesive system according to the present invention. Test Objective: To evaluate the rupture and release characteristics of the microcapsules under stirring and shearing action, and to verify the controllability of the sustained-release mechanism. Test Principle: The change in the content of free glacial acetic acid in the system over time is determined by titration to reflect the rupture and release kinetics of the microcapsules. Experimental Method: Five parts by mass of the microcapsule component were dispersed in the adhesive mother liquor. Stirring was carried out continuously at 25℃ and a stirring speed of 300 r / min. Samples were taken at 0, 10, 30, 60, 120, and 240 minutes. The content of free glacial acetic acid was determined by acid-base titration, and titrated to the phenolphthalein endpoint with sodium hydroxide standard solution. The glacial acetic acid release rate was calculated. Key Parameters: Stirring speed 300 r / min, temperature 25℃, titrant: 0.1 mol / L NaOH solution. Data Processing: Release rate = (mass of free glacial acetic acid / mass of glacial acetic acid in the microcapsule component) × 100%, and the average value ± standard deviation of three parallel experiments was taken.
[0082] Experiment 6: Evaluation of Appearance Defects in Adhesive Film Test Object: The adhesive film formed after the PMMA adhesive of this invention is coated and cured. Test Objective: To evaluate the defoaming ability and appearance quality of the adhesive film during rapid evaporation and drying, and to verify the low-defect design of the high-solids-content system. Test Principle: The number and area ratio of bubbles in the adhesive film are statistically analyzed using an optical microscope. Experimental Method: The adhesive is uniformly coated onto a glass substrate with a wet film thickness of 200µm. It is then naturally dried for 24 hours at 25℃ and 50% relative humidity. After drying, images are taken at 100x magnification using an optical microscope, randomly selecting 10 fields of view. Bubbles larger than 10µm in diameter are identified using image analysis software, and the bubble number density and bubble area ratio are statistically analyzed. Key Parameters: Wet film thickness 200µm, drying time 24 hours, bubble identification threshold 10µm. Data Processing: Bubble rate = total bubble area / total field of view area × 100%, taken as the average ± standard deviation of the 10 fields of view.
[0083] Figure 1 The plot shows the particle size difference distribution q(d) for Example 1 and Comparative Example 7. The parameters are fixed: consistent particle size statistical method, logarithmic scale of particle size d on the x-axis, and normalized representation of the difference distribution q(d) on the y-axis. The parameter is changed when the sample is switched from Example 1 to Comparative Example 7. The distribution peaks of Example 1 are concentrated in a smaller particle size range and have a narrower distribution width. The peaks of Comparative Example 7 are shifted to the right and show a larger proportion of particle size. This indicates that Example 1 forms a finer and more uniform dispersion system, which is beneficial for obtaining more stable structure and performance consistency. From a distribution perspective, this demonstrates that the preparation route of this scheme can effectively control particle size.
[0084] Figure 2The plots show the cumulative particle size distribution Q(d) for Example 1 and Comparative Example 7. The parameters are fixed: the particle size statistical method is consistent; the horizontal axis represents the logarithmic scale of particle size d; and the vertical axis represents the cumulative distribution Q(d), ranging from 0 to 1. The parameter is changed from Example 1 to Comparative Example 7. The Q(d) curve for Example 1 rises rapidly in the smaller particle size range and reaches a high cumulative proportion earlier, indicating that under the same statistical caliber, its smaller particle size component has a higher proportion and the overall particle size level is lower. The curve for Comparative Example 7 shifts later overall, representing an increase in the proportion of larger particle sizes. The cumulative distribution and differential distribution corroborate each other, proving that this method can control the particle size within a more favorable range and improve batch repeatability.
[0085] Figure 3 The above are the superimposed FTIR spectra of Example 1 and Comparative Example 6, with the following parameters fixed: Fourier transform infrared spectroscopy as the characterization method, and wavenumber as the abscissa. The samples are arranged conventionally from high to low, with absorbance (au) on the ordinate. The parameter variation is when the sample is switched from Example 1 to Comparative Example 6. Example 1 shows a clearer contribution from functional groups in the peak shape and intensity of the hydroxyl-related broad peak region and characteristic peak regions such as carbonyl groups, while the corresponding regions of Comparative Example 6 have weaker signals or significant differences in peak shape. This indicates that Example 1 is more sufficient in terms of the expected chemical action or structural introduction, and can support the material basis for the subsequent performance establishment. From the chemical structure level, it proves that the component design and reaction control of this scheme are effective.
[0086] Figure 4 The DSC plots for Example 1 and Comparative Example 3 are shown. The fixed parameters are: differential scanning calorimetry (DSC) as the characterization method; temperature (°C) on the x-axis; heat flux (au) on the y-axis; and endothermic / exothermic characteristics along a set direction. The variable parameter is: the sample is switched from Example 1 to Comparative Example 3, and their thermal transition behavior is compared. Example 1 exhibits a clearer and more identifiable baseline step characteristic in the glass transition temperature range, while the thermal events related to volatilization and release are weaker or more controllable, indicating that Example 1 has higher phase stability and that small molecule release behavior is suppressed. Comparative Example 3 shows weaker transition characteristics or more pronounced thermal events, suggesting that the system is more prone to structural relaxation or volatilization migration. The thermal analysis results demonstrate, from the perspective of thermal stability and phase maintenance, that this scheme can construct a more stable material state and support performance reliability.
[0087] Figure 5The image shows a physical sample of the PMMA adhesive with viscosity controlled by glacial acetic acid in Example 1. The fixed parameters were: 17 parts by mass of PMMA, 75 parts by mass of solvent system (60 parts by mass of ethyl acetate and 15 parts by mass of acetone), 5 parts by mass of PMMA-coated glacial acetic acid microcapsules, and mixing for 30 minutes at 25°C and 300 r / min after adding the microcapsules, followed by degassing for 20 minutes under a vacuum of 0.045 MPa. The variable parameter was the amount of glacial acetic acid, adjusted from 2 to 15 parts by mass to obtain different viscosities. In Example 1, with 8 parts by mass of glacial acetic acid, the adhesive was a macroscopically homogeneous, highly viscous system without visible layering. The viscosity was measured at a shear rate of 25°C. Under the given conditions, the viscosity reached 15000 mPa·s, corresponding to a mass ratio of glacial acetic acid to PMMA of 0.47:1, demonstrating that the viscosity can be controlled and the system is stable and processable by adjusting the amount of glacial acetic acid used.
[0088] Figure 6 The image shows a scanning electron microscope (SEM) image of the PMMA-coated glacial acetic acid microcapsule components from Example 1. The fixed parameters were the following microcapsule preparation conditions: oil phase preparation temperature 35°C, stirring speed 500 r / min for 4 hours; emulsification temperature 22°C, shearing speed 6500 r / min for 6 minutes; aqueous phase polyvinyl alcohol mass fraction 1.64 wt% at 75°C, stirring speed 400 r / min for 1.5 hours; encapsulation stirring speed 850 r / min for 35 minutes; vacuum distillation temperature 32°C, absolute pressure 0.045 MPa to remove ethyl acetate for 3 hours and recover to 95% of the feed amount; centrifugation speed 5500 r / min for 12 minutes; and drying at 45°C, absolute pressure 0.018 MPa for 14 hours. The variable parameters were the SEM observation magnification from low to high to characterize surface details and cross-sectional structure. Scanning electron microscopy showed that the microcapsule particles were mainly spherical with an average particle size of 40 µm, consistent with the quality control. The particle surface was continuous overall, with slight wrinkles and local depressions caused by drying shrinkage. The cross-section showed core-shell characteristics, which was consistent with the desolventizing and drying results of 35% encapsulation rate and 0.25 wt% residual ethyl acetate. This proved that the set emulsification and desolventizing process could form a stable PMMA shell and achieve effective encapsulation of glacial acetic acid.
[0089] Figure 7The image shown is a transmission electron microscope (TEM) image of the PMMA-coated glacial acetic acid microcapsule component from Example 1. The parameters were fixed: the sample was taken from dried PMMA-coated glacial acetic acid microcapsules, the mass ratio of glacial acetic acid to PMMA in the microcapsule component was 0.64:1, and the encapsulation and desolvation conditions were maintained at 32°C and 0.045 MPa, with ethyl acetate removed to 95% recovery. The parameters were varied by changing the observation area of the TEM from the overall shell to the local microstructure of the shell to characterize the shell continuity and porosity. The TEM revealed that the microcapsule shell was a continuous phase with a gradient characteristic from relatively dense on the outside to relatively loose on the inside, and localized nanoscale pores and micropores. This structure is consistent with the phase separation and pore formation process induced by solvent removal and provides channels and rupture sensitivity for the release of glacial acetic acid under stress or solvent action, demonstrating that the PMMA-coated structure has a microscopic basis for achieving sustained release and gradual viscosity improvement.
[0090] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1-4 achieved precise viscosity control within the range of 500-50000 mPa·s by adjusting the amount of glacial acetic acid. Moreover, the viscosity change rate was controlled within 5% after 7 days of storage, demonstrating excellent storage stability. At the same time, the shear strength reached 6.2-10.5 MPa, and the creep was controlled within 1.5%, reflecting an effective balance between low viscosity construction and high strength bonding. In contrast, Comparative Example 1, due to its low PMMA content, exhibited low initial viscosity and a significant 15.3% viscosity decrease during storage, with a shear strength of only 3.8 MPa and a creep rate as high as 3.2%, indicating insufficient system stability and mechanical properties. Comparative Example 2, due to its high PMMA content, resulted in excessively high viscosity and a bubble rate as high as 8.2%, making degassing difficult. Comparative Examples 3 and 4 suffered from viscosity control failure and deteriorated storage stability due to an imbalance in the amount of glacial acetic acid used. Comparative Example 6, lacking microcapsule components, experienced a significant 22.4% viscosity decrease during storage and lacked time-varying rheological control capabilities. Comparative Example 7, due to improper microcapsule preparation process, resulted in excessively large particle size, low encapsulation efficiency, excessively rapid release rate, and a bubble rate as high as 6.8%. Comparative Example 8 suffered from poor storage stability due to an improper solvent system. These examples, through synergistic optimization of PMMA dosage, glacial acetic acid dosage, microcapsule component dosage, and their preparation process, successfully resolved the contradictions between low-viscosity construction, high-strength bonding, storage stability, and time-varying rheological control, verifying the superiority of the technical solution.
[0091] Table 1 Performance summary of examples and comparative examples
[0092] Example 1 15000±450 15300±520 2.0±0.8 8.5±0.4 0.8±0.2 1.2±0.3 18±3 Example 2 35000±1200 35800±1350 2.3±0.7 9.8±0.5 0.5±0.1 0.8±0.2 12±2 Example 3 3000±180 3150±210 5.0±1.2 6.2±0.3 1.5±0.3 2.8±0.5 28±4 Example 4 45000±1600 46200±1750 2.7±0.9 10.5±0.6 0.3±0.1 0.5±0.1 8±2 Comparative Example 1 8500±650 7200±800 -15.3±3.5 3.8±0.5 3.2±0.6 5.5±1.2 45±6 Comparative Example 2 68000±3200 72000±3800 5.9±2.1 6.5±0.8 2.8±0.5 8.2±1.8 5±1 Comparative Example 3 42000±2100 43500±2250 3.6±1.3 5.2±0.6 2.1±0.4 3.5±0.8 3±1 Comparative Example 4 1200±150 950±180 -20.8±4.2 4.5±0.4 4.8±0.9 12.5±2.5 62±8 Comparative Example 5 18000±850 19500±950 8.3±2.5 7.2±0.5 1.2±0.3 2.0±0.4 5±1 Comparative Example 6 16500±700 12800±1100 -22.4±5.1 7.8±0.4 1.1±0.2 1.5±0.3 0±0 Comparative Example 7 14500±550 15200±620 4.8±1.5 7.5±0.5 1.4±0.3 6.8±1.5 35±5 Comparative Example 8 22000±1100 18500±1350 -15.9±3.8 5.8±0.6 2.5±0.5 9.5±2.2 22±4
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A PMMA adhesive with viscosity controlled by glacial acetic acid, characterized in that, The adhesive comprises, by weight, the following: PMMA 10–25 parts by weight; 2–15 parts by weight of glacial acetic acid; Solvent system 50–100 parts by mass; and 0.5–10 parts by weight of PMMA-coated glacial acetic acid microcapsule component after drying; The solvent system is selected from one or both of ethyl acetate and acetone; the 10–25 parts by weight of PMMA do not include PMMA in the microcapsule component, the 2–15 parts by weight of glacial acetic acid do not include glacial acetic acid in the microcapsule component, and the 50–100 parts by weight of the solvent system do not include residual solvent in the microcapsule component; furthermore, the adhesive is used at a temperature of 25°C and a shear rate of 10 s. -1 Under these conditions, the viscosity measured by a rotational viscometer was 500–50000 mPa·s, and the viscosity was adjusted by changing the specific amount of glacial acetic acid in the range of 2–15 parts by mass. The PMMA-coated glacial acetic acid microcapsule component was prepared through the following steps: A1, Preparation of the oil phase: Add 5–20 parts by weight of PMMA to 80–200 parts by weight of ethyl acetate and stir to dissolve, thus obtaining the PMMA oil phase; A2, preparation and emulsification of the core phase: 5-40 parts by weight of glacial acetic acid are added to the PMMA oil phase, and sheared for 2-10 minutes at a shearing speed of 3000-10000 r / min to obtain a pre-emulsion with a core material dispersion. A3, Preparation of aqueous phase: Add 2-20 parts by weight of polyvinyl alcohol to 200-1000 parts by weight of deionized water and stir to dissolve to obtain the polyvinyl alcohol aqueous phase; A4, Encapsulation and Desolventizing: The pre-emulsion is added to the polyvinyl alcohol aqueous phase and stirred for 10–60 min at a stirring speed of 300–1500 r / min to form an emulsion. Then, ethyl acetate is removed under conditions of 20–45℃ and 0.01–0.08 MPa absolute pressure by vacuum distillation and recovery of ethyl acetate through a condenser until the cumulative recovered ethyl acetate mass reaches 90–99% of the ethyl acetate mass of the feed. A5, Post-processing: After solid-liquid separation, the obtained system is washed with deionized water 1–5 times and dried at a temperature of 35–55℃ and an absolute pressure of 0.005–0.03MPa for 4–24h to obtain the PMMA-coated glacial acetic acid microcapsule component. The mass ratio of 2–15 parts by mass of glacial acetic acid to 10–25 parts by mass of PMMA is 0.08:1–0.8:
1.
2. The adhesive according to claim 1, characterized in that, The quality control parameters for the PMMA-coated glacial acetic acid microcapsule component are as follows: particle size of 1–80 µm, encapsulation rate of glacial acetic acid of 10–60%, wherein the encapsulation rate is the ratio of the mass of glacial acetic acid in the microcapsule component to the mass of glacial acetic acid fed into the feed, and the residual ethyl acetate is not higher than 0.5 wt%, wherein the wt% is based on the total mass of the dried microcapsule component.
3. The adhesive according to claim 1, characterized in that, The mass ratio of glacial acetic acid to PMMA in the PMMA-coated glacial acetic acid microcapsule component is 0.5:1–3:1, where the mass of glacial acetic acid is the mass of glacial acetic acid in the microcapsule component, and the mass of PMMA is the mass of PMMA, the shell material of the microcapsule; in step A3, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous phase is 0.2–9.1 wt%, where the mass fraction is calculated as polyvinyl alcohol mass / (polyvinyl alcohol mass + deionized water mass) × 100%; and in step A4, the time for removing ethyl acetate is 0.5–6 h.
4. The adhesive according to claim 1, characterized in that, The solvent system consists of one or both of ethyl acetate and acetone, and the sum of the mass parts of ethyl acetate and acetone is 50–100 parts by mass, wherein ethyl acetate is 50–100 parts by mass and acetone is 0–50 parts by mass.
5. A method for preparing a PMMA adhesive with viscosity controlled by glacial acetic acid as described in any one of claims 1-4, characterized in that, Includes the following steps: S1 provides PMMA-coated glacial acetic acid microcapsule components; S2, Preparation of adhesive masterbatch: Add 10–25 parts by weight of PMMA to 50–100 parts by weight of solvent system and stir to dissolve, to obtain adhesive masterbatch without glacial acetic acid and without microcapsule components, wherein the solvent system is selected from one or both of ethyl acetate and acetone; S3, Add glacial acetic acid: Add 2-15 parts by weight of glacial acetic acid to the glue stock solution and mix; S4, Add microcapsule component: Add 0.5–10 parts by weight of the PMMA-coated glacial acetic acid microcapsule component to the system obtained in step S3 and mix evenly to obtain the adhesive; In step S3, the amount of glacial acetic acid is controlled to ensure that the resulting adhesive is heated to 25°C and has a shear rate of 10s. -1 The viscosity was adjusted to 500–50000 mPa·s under the specified conditions.
6. The method according to claim 5, characterized in that, The dissolution temperature in step S2 is 20–50°C and the dissolution time is 0.5–8 h. The temperature at which the microcapsule component is added in step S4 is 15–35°C. The solvent system in step S2 is composed of one or both of ethyl acetate and acetone, and the sum of the mass parts of ethyl acetate and acetone is 50–100 parts by mass, wherein ethyl acetate is 50–100 parts by mass and acetone is 0–50 parts by mass.
7. The method according to claim 5, characterized in that, The addition time of glacial acetic acid in step S3 is 1–20 min, and the mixing time in step S4 is 5–60 min.
8. The method according to claim 5, characterized in that, After the mixture is homogeneous in step S4, it is degassed for 10–30 minutes under vacuum conditions with an absolute pressure of 0.01–0.08 MPa.
Citation Information
Patent Citations
Acrylic glue and preparation method thereof
CN112266748A
PMMA (polymethyl methacrylate) glue with high ionic conductivity and preparation method thereof
CN119775930A
Long-acting environment-friendly organic glass adhesive
CN104673145A
Microcapsule material coated with organic dicarboxylic acid and preparation method and application of microcapsule material
CN105080443A